ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN KELUARGA NELAYAN (Studi Kasus Di Desa Pasar Seblat) - Dedi Prayetno; Imron Rosyadi (Jurnal Saintifik (Multi Science Journal), 2022)
This study aims to determine the magnitude of the influence of the number of family dependents on the welfare of the fishermen's family, to determine the magnitude of the effect of working hours on the welfare of fishermen's families, to determine the magnitude of the influence of fishing trips to fishermen family welfare, to determine the magnitude of the effect simultaneously on the number of dependents of the family, working hours. and the distance to the welfare of fishermen families in Pasar Seblat Village. The population of this research is the fishing families of Pasar Seblat Village, amounting to 127 families, from the calculation using the Slovin formula with a margin of error of 5%, it can be seen that the number of samples in this study was 96 respondents. This type of research in this research is in the form of quantitative descriptive research.The results of this study indicate that the variable number of family dependents (X1) has a positive and significant effect on family welfare (Y) as indicated by a positive regression coefficient of 0.787 with a sig value of 0.000 <0.050. The working hour variable (X2) has a positive and significant effect on family welfare (Y) as indicated by the positive regression coefficient of 0.239 with a sig value of 0.003 <0.050. The operational cost variable (X3) has a positive and significant effect on family welfare (Y) as indicated by the positive regression coefficient of 0.168 with a sig value of 0.006 <0.050. The result of F states that the number of family dependents, working hours and operational costs simultaneously have a positive and significant effect on the welfare of fishermen families in Pasar Sebelat Village. The regression coefficient value is 1.485 with a sig value of 0.000 <0.050. The magnitude of the influence of the number of family dependents, working hours and operational costs on the welfare of fishermen's families 80.2% and 19.8% is influenced by other factors that are not disclosed in this study. ABSTRAK Penelitian ini bertujuan untuk mengetahui besarnya pengaruh jumlah tanggungan keluarga terhadap kesejahteraan keluarga nelayan, untuk mengetahui besarnya pengaruh jam kerja terhadap kesejahteraan keluarga nelayan, untuk mengetahui besarnya pengaruh usaha penangkapan ikan. perjalanan kesejahteraan keluarga nelayan, untuk mengetahui besarnya pengaruh secara simultan terhadap jumlah tanggungan keluarga, jam kerja. dan jarak kesejahteraan keluarga nelayan di Desa Pasar Seblat. Populasi dalam penelitian ini adalah keluarga nelayan Desa Pasar Seblat yang berjumlah 127 KK, dari perhitungan menggunakan rumus Slovin dengan margin of error 5% terlihat bahwa jumlah sampel dalam penelitian ini adalah 96 responden. . Jenis penelitian dalam penelitian ini adalah berupa penelitian deskriptif kuantitatif. Hasil penelitian ini menunjukkan bahwa variabel jumlah tanggungan keluarga (X1) berpengaruh positif dan signifikan terhadap kesejahteraan keluarga (Y) yang ditunjukkan dengan koefisien regresi positif sebesar 0,787 dengan nilai sig 0,000 < 0,050. Variabel jam kerja (X2) berpengaruh positif dan signifikan terhadap kesejahteraan keluarga (Y) yang ditunjukkan dengan koefisien regresi positif sebesar 0,239 dengan nilai sig 0,003 < 0,050. Variabel biaya operasional (X3) berpengaruh positif dan signifikan terhadap kesejahteraan keluarga (Y) yang ditunjukkan dengan koefisien regresi positif sebesar 0,168 dengan nilai sig 0,006 < 0,050. Hasil F menyatakan bahwa jumlah tanggungan keluarga, jam kerja dan biaya operasional secara simultan berpengaruh positif dan signifikan terhadap kesejahteraan keluarga nelayan di Desa Pasar Sebelat. Nilai koefisien regresi adalah 1,485 dengan nilai sig 0,000 < 0,050. Besarnya pengaruh jumlah tanggungan keluarga, jam kerja dan biaya operasional terhadap kesejahteraan keluarga nelayan 80,2% dan 19,8% dipengaruhi oleh faktor lain yang tidak diungkapkan dalam penelitian ini.